Psychological wellbeing and mental health amongst medical undergraduates: A descriptive study assessing more than 1, 000 medical students in Sri Lanka. (September 2022) - Dahanayake, Dulangi; Rajapakse, Harshini; Wickramasinghe, Anuprabha; Chandradasa, Miyuru; Rohanachandra, Yasodha; Perera, Sayuri; Nillo, Anne-Marie; Molodynski, Andrew
Background: Studies from around the world have shown higher rates of anxiety, depression, alcohol and other drug use, and burnout in medical students. Aims: The aim of this study was to identify the socio-demographic factors and severity of difficulties Sri Lankan medical students face regarding psychological wellbeing and burnout. Method: This one-off survey used a cross-sectional design, assessing substance use, psychological wellbeing, and burnout using the CAGE, GHQ-12, and OLBI. The survey was open to all medical students in six universities in Sri Lanka. Chi-square analysis was used to assess the statistical significance related to categorical dependent variables and one-way ANOVA for continuous dependent variables. Results: A higher prevalence of diagnosed mental health conditions was found following admission to the medical course in comparison prior to admission. Sixty-two percent of students had a score of more than 2 on the GHQ-12 indicating caseness. The OLBI identified exhaustion in 79% of students. The CAGE questionnaire was positive in 4.8% of students. Conclusions: Only a small proportion of students are recognizing their mental health difficulties and seeking help. Further understanding is required as to why this is, as well as re-evaluation of the demands of the curriculum. Effective ways of regularly identifying and providing practical and evidence-based support for mental health problems in medical and other undergraduates need to be identified and introduced.